2010
DOI: 10.1002/qj.686
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of convection‐related parameters on surface and boundary‐layer conditions over complex terrain

Abstract: The field campaign 'Convective and Orographically-induced Precipitation Study' (COPS) was performed in south-western Germany and eastern France in summer 2007. Within the COPS context this study focused on the process chain of soil moisture, surface fluxes, conditions of the convective boundary layer (CBL), and convection-related parameters.The results were different for valley and mountain sites. Only in the Rhine valley did the ratios of sensible and latent heat to the net radiation at the surface, H 0 /Q 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 37 publications
5
35
2
Order By: Relevance
“…The process chain of soil moisture, surface fluxes, CBL conditions, and convection-related parameters over complex terrain are analysed by Hauck et al (2011) and Kalthoff et al (2011). The results were different for valley and mountain sites.…”
Section: Land-surface Exchange Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The process chain of soil moisture, surface fluxes, CBL conditions, and convection-related parameters over complex terrain are analysed by Hauck et al (2011) and Kalthoff et al (2011). The results were different for valley and mountain sites.…”
Section: Land-surface Exchange Processesmentioning
confidence: 99%
“…The frequency of low CIN was higher in the Black Forest than in the Rhine valley, which facilitates convection initiation over the mountain sites (e.g. Kalthoff et al, 2011;Behrendt et al, 2011).…”
Section: Land-surface Exchange Processesmentioning
confidence: 99%
“…The influences on simulated precipitation is more complex and depends strongly on the chosen case and domain. A dependency of all convective indices on the equivalent potential temperature was found by Kalthoff et al (2011) over different orographic terrains. However, convection was predominantly initiated over mountain, independent of the instability indices, but with smaller 20 convective inhibition.…”
Section: Introductionmentioning
confidence: 93%
“…Significant differences between planetary boundary driven and synoptic forced conditions could not be detected. Further studies by Kalthoff et al (2011) and Hauck et al 15 (2011) over orographic complex terrain investigate the role of orographic effects in the synergy of soil moisture-precipitation feedbacks. Hauck et al (2011) determines large systematic differences between modelled and observed soil moisture.…”
Section: Introductionmentioning
confidence: 98%
“…Detailed studies by Kalthoff et al (2009) and Behrendt et al (2011) on COPS-IOP 8b investigate the initiation of convection by superposition of a synopticscale convergence and a regional-scale mountain range and thermally induced convergence. The dependence of convection-related parameters on surface and boundarylayer conditions over complex terrain during the COPS period was investigated by Kalthoff et al (2011).…”
Section: Introductionmentioning
confidence: 99%